Communication ethics of content creators in the new media era based on Bugis Makassar local wisdom - Zulkarnain Hamson; Muhammad Akbar; Syamsuddin Aziz (Universitas Muhammadiyah Malang, 2025)
This study investigates the incorporation of Bugis-Makassar's local wisdom values into content creators’ digital communication ethics. In the contemporary era, where social media serves as a platform for expression and community building, this study sought to develop a communication ethics model grounded in local values. Values such as